In situ Analysis of Tissue Factor-Dependent Thrombin Generation in Human Atherosclerotic Vessels - Westmuckett, Andrew D.; Lupu, Cristina; Goulding, David A.; Das, Saroj; Kakkar, Vijay V.; Lupu, Florea (Thrombosis and Haemostasis, 2000)
Tissue factor (TF) is expressed in human atherosclerotic plaques where it may contribute to the thrombogenicity of the lesions and their progression toward unstable syndromes and acute myocardial infarction. In this study we tested the hypothesis that thrombin generation takes place in the lesion. Localisation of TF, factor VII (FVII), factor X/Xa (FX/Xa), thrombin, thrombin receptor PAR-1 and FXa receptor EPR-1 was done by immunostaining, ligand binding, or immunogold electron microscopy. Quantitation of TF antigen was done using a modified ELISA on fixed tissue sections. The amount of antigen was correlated with the pattern and intensity of immunostaining as detected on consecutive sections using confocal microscopy. TFdependent generation of FXa on cryosections was used to assess the functional activity of TF. Active thrombin was detected using hirudin as a specific probe, followed by anti-hirudin IgG. Our light microscopy and immunogold electron microscopy results showed that the factors involved in TF-dependent coagulation are localised in atherosclerotic plaques in close proximity and colocalise with active thrombin and fibrin deposits. We have detected 3 to 7-fold increase of TF antigen and TF-dependent FXa generation in atherosclerotic vessels as compared with controls. Hirudin binding proved that active thrombin is present within the lesions. In conclusion, our data show that active coagulation factors are generated within atherosclerotic lesions and co-localise with their cellular receptors. These findings may suggest possible roles of the TF-dependent coagulation pathway in the intramural fibrin deposition and the progression of the atherosclerotic lesions.
Keywords: Atherosclerosis; coagulation; immunogold; tissue factor; thrombin receptor; factor Xa receptor